Evaluation of cowpea [Vigna unguiculata (L) Walp.] lines for high grain and fodder yields in the dry season of Niger republic - Souleymane Abdou (Heliyon, 2022)
Cowpea grains constitute a nutritious food to humans, while resource-poor farmers use its fodder and shell in fattening livestock during the dry season in Niger. Owing to the high price of these commodities, especially in the hot, dry season, the development and adoption of dual-purpose varieties adapted that period may significantly lower the cost of cowpea products to farmers. To that end, 12 cowpea genotypes were evaluated for high grain and forage yield at three INRAN research stations during the hot, dry season of 2021. The data collected were analyzed with R software and the results revealed significant differences among genotypes for grain and fodder yields. IN17_142 and IN15_62 turned out to be the best performing cultivars with 1198.3 kg/ha and 1187.5 kg/ha as mean grain yield and 3790.0 kg/ha and 3542.0 kg/ha in terms of mean fodder yield. However, above 2 and 6 tons mean grain and fodder yields per hectare were recorded by each of these two genotypes at Maradi. High positive relationships were detected between grain and fodder yields, as a result, the winning lines are the same for the two traits. Dual-purpose varieties suited for cowpea production in the hot dry season of Niger are detected in this work and its adoption by farmers may help boost the production.